THE THEORETICAL PRINCIPLES OF JUSTICE WITHIN THE PENAL ASPECT - Kristina Sawen (Yuridika, 2017)
Justice will be fulfilled when the restraint on actions to benefit themselves by way of seizing what belongs to someone else is or reject what was supposed to be given to others.Justice will be fulfilled when self-restraint are applied to on actions that will only be self-benefiting for the said individuals by way of seizing someone else’s belongings or rejecting what is supposed to be given to others. Justice will be seen in the legal provisions governing and being framed in managing the human life even if that provision is still in the form of ideas that poured in through the legal provisions of the country. Justice can be seen in legal provisions that govern and frame the human’s life even if that provision is still in the form of ideas that are subscribed in the legal provisions of the country. The threat of sanctions contained in the law as one element of a crime, is also a manifestation of the value of the balance between the prohibition or the permissibility of things which will manifest themselves in a sanction when a violation of these provisions. The threat of a sanction that is contained in the law, as an element of crime, is also a form of manifestation of the accessibility of a certain value of balance between prohibition or permissibility which will be visible in the form of a sanction when a violation of these provisions occurs. As a value of balance between the ban and the threat of sanctions would also form the idea of the values of justice in law, which is expected to be obeyed by the people. The value of a balance between the prohibitions or threats will also form the values of justice in law, which is expected to be adhered to by by the people. So the sosial order and security of living together can be met.The importance of justice seen as essential virtues of that must be firmly held and at the same time the spirit of the basis of various institutions basic social a society .It means give it a chance in a fair manner and the same for all people to develop and enjoy of self-respect and dignity as human beings who is not measured with riches economical so that it should be understood that justice deep broader beyond the economic status of a person As such, the social order and security of living together can be met. The importance of justice is seen as the essence of virtues that has to be followed upon and should be the basis of motivation of various basic social institution of a society. This means that each individuals are given the same possibility in a fair manner to develop and enjoy their self-respect and dignity as human beings; not by measuring the economical strength or means; therefore it has to be understood that justice runs deeper than the economic status of a person.